Biomechanical Effects of Menopause in Ovariectomized Rats' Femurs (vol 30, pg 62, 2014) - Okyay, Ayse Guler; Kavak, Servet; Turktas, Ugur; Alkis, Ismet; Guner, Savas; Aksakal, Bunyamin (Informa Healthcare, 2014)
[Abstract Not Available]